2013
DOI: 10.1038/onc.2013.194
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma metastasis: new concepts and evolving paradigms

Abstract: Melanoma progression is typically depicted as a linear and stepwise process in which metastasis occurs relatively late in disease progression. Significant evidence suggests that in a subset of melanomas, progression is much more complex and less linear in nature. Epidemiologic and experimental observations in melanoma metastasis are reviewed here and are incorporated into a comprehensive model for melanoma metastasis, which takes into account the varied natural history of melanoma formation and progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
126
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(132 citation statements)
references
References 168 publications
1
126
0
5
Order By: Relevance
“…The slow drug release from NDHCs with higher dendrimer-NP ratio was probably due to the thicker and denser nanocapsule shell that caused by the high Arg-AuNP: dendrimer linker ratio. Importantly, the PTX release kinetic study showed no evidence of burst release of drug, making NDHCs excellent candidates for controlled drug delivery [16].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The slow drug release from NDHCs with higher dendrimer-NP ratio was probably due to the thicker and denser nanocapsule shell that caused by the high Arg-AuNP: dendrimer linker ratio. Importantly, the PTX release kinetic study showed no evidence of burst release of drug, making NDHCs excellent candidates for controlled drug delivery [16].…”
Section: Resultsmentioning
confidence: 99%
“…The in vivo antitumor efficacy of PTX-loaded NDHC was preliminarily investigated with a B16F10 melanoma tumor model that has a high level of angiogenesis [19,20], providing a model for passive tumor targeting. We initially studied the biodistribution of NDHCs in mice organs, and found that a substantial amount of NDHC was accumulated in tumor, as well as other organs including liver, spleen and kidneys (Supplementary Figure 10).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[99] BM are a frequent complication in melanoma patients, and unlike in other solid tumors, arise independently from other visceral metastasis. Many melanoma patients are cured after excision of the primary tumor but, in some cases, a disease recurrence appears in different sites as metastatic lesions [100] suggesting that melanoma cells had already spread before excision of the primary tumor.…”
Section: Breast Cancermentioning
confidence: 99%
“…Dans de nombreux cas, des cellules cancéreuses métastatiques seraient même présentes avant que la tumeur primitive ne soit détectée cliniquement. Dans le mélanome cutané, l'analyse du profil des rechutes métastatiques après exérèse de la lésion primitive est également en faveur d'un modèle de dissémination précoce [8]. Dans le mélanome uvéal, la …”
Section: Dans Certains Cancers La Dissémination Des Cellules Cancéreunclassified